Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Find the distance between (1, 3) and (-2, -6) and put it in simplest radical form

Sagot :

Answer:

  • [tex]\tt 9.48[/tex]

Step-by-step explanation:

(1,3) and (-2,-6)

[tex]\tt Distance= \sqrt{(-6-3)^2+(-2-1)^2}[/tex]

[tex]\tt =\sqrt{9^2+3^2}[/tex]

[tex]\tt =\sqrt{81+9} =\sqrt{90}[/tex]

[tex]\tt Distance=\sqrt{90} =9.48[/tex]

Esther

Answer:

[tex]D=\sqrt{90}\ or\ D=9.49[/tex]

Step-by-step explanation:

[tex]D=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\\\D=\sqrt{(-2-1)^2+(-6-3)^2}\\\\D=\sqrt{(-2-1)^2+(-6-3)^2} \\\\D=\sqrt{(-3)^2+(-9)^2} \\\\D=\sqrt{9+81} \\\\D=\sqrt{90}\\\\D=9.49[/tex]

Hope this helps!